Pemetaan Syarah Shahih Muslim Berdasarkan data Bibliometrik - Jauharah Khairun Nisa (Gunung Djati Conference Series, 2023)
Shahih Muslim's Syarah is a book that explains, comments on, and elaborates on the original book, Sahih Muslim. Syahrah Sahih Muslim is a very famous (popular) hadith syarah among Muslims. This article only attempts to complement existing studies, namely by comprehensively explaining the Shariah of Sahih Muslim. By including the data that has been examined by the author and the explanation. This study uses a bibliometric approach by using mapping analysis keywords using bibliometrics. This study presents data findings using the keyword Syarah Saheeh Muslim, as reflected in the research that has been described. This study investigates the categories of research, the development of publications, the researchers who play an active role, and the dominating places of publication. The results of the research show that the Syahih Muslim Syarah is still developing and being researched by many people. The research category Syarah Saheeh Muslim is dominantly researched in the fields of philosophy and the study of religions. The development of Syarah Shahih Muslim research publications tends to increase every year with the highest number of publications occurring in 2018. In the Syarah Saheeh Muslim research, the researcher who is dominant and plays an active role in publishing Syaih Muslim articles, namely Benny Afwadzi, has published 6 articles. Place of publication of Syarah Shahih Muslim's research is dominated by the field of Diroyah Journal of Hadith Studies by publishing 18 articles.